Implementation of Islamic Boarding School Financial Management In The Era Of Society 5.0 (Case Study at Bumi Damai Islamic Boarding School Al-Muhibbin Jombang) - Lailatul Rifqoh Izzati; Muhammad Ekhsan; Lillahi Akbar Jihadi; Achmad Yusuf Bagus Styawan (Mudir : Jurnal Manajemen Pendidikan, 2023)
PP. Bumi Damai al Muhibbin Jombang, in maintaining the existence and stability of Islamic boarding schools, various efforts are needed in it, one of which is managing Islamic boarding schools' finances. pp. Bumi Damai al Muhibbin Jombang with relatively cheap entry and monthly fees is able to manage finances well. So from here the researcher wants to examine further and in depth how the financial management system in PP. Bumi Damai al Muhibbin so that PP. Bumi Damai al Muhibbin Jombang is the most existing cottage and has many devotees. In this study, researchers used descriptive qualitative methods. In Islamic boarding school financial management, PP. Bumi Damai al Muhibbin does a number of things including doing budgeting based on the annual needs that have been determined at the annual meeting. In terms of implementation, there are two things that are done, namely income consisting of monthly payments, donations, pesantren business profits and so on, while expenses have been regulated in such a way that they are adjusted to the sub-income sub-income so that between income and expenses will be balanced. In carrying out supervision the head of the department continuously supervises directly through performance and reports. Financial evaluation is carried out three times, namely quarterly, semester and annually. So that's where PP. Bumi Damai al Muhibbin is able to manage its finances properly and efficiently so that it is able to attract prospective students to study at the pesantren. And the benefits obtained by researchers are the knowledge of effective and efficient financial management.